Pengaruh Work-Life Balance Dan Time Management Terhadap Kinerja Karyawan Perusahaan XYZ - Perkasa, Ully Nuha; Husadha, Cahyadi; Kurniawan, Dody (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The COVID-19 pandemic triggered a shift in work patterns, including the implementation of Work From Home and hybrid work systems. This study aims to examine the effect of Work-life Balance (X1) and Time Management (X2) on Employee Performance (Y) in the B2C and B2B Divisions of Perusahaan XYZ Indonesia, located at TCC Batavia Tower One, Jakarta. A quantitative approach was used, employing a survey method with saturated sampling, involving all 50 employees. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with SPSS version 25. The results indicate that both X1 and X2 have a positive and significant influence on Y. The post-pandemic hybrid work policy (two days per week) is considered effective in maintaining employee performance. This research provides valuable insights for developing flexible work policies in the modern work environment.